2011
DOI: 10.1007/s11240-011-0056-y
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing Agrobacterium-mediated transformation of switchgrass cultivars

Abstract: To optimize Agrobacterium tumefaciens-mediated transformation, factors influencing gene delivery, selection of transformed cells, and plant regeneration were investigated using two major switchgrass cultivars, including a lowland tetraploid cultivar Alamo and an upland octoploid cultivar Cave-in-Rock (CIR). Transient expression studies monitored by histochemical b-glucuronidase assay in seedling segments indicated that A. tumefaciens strain EHA105 was more effective in gene delivery than LBA4404 or GV3101. Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 35 publications
0
47
0
Order By: Relevance
“…So far no genetic transformation of upland cultivars has been reported. Even callus regeneration is very difficult to achieve (Song et al 2012;Nageswara-Rao et al 2013). Thus, establishment of a highly efficient and amenable plant regeneration and transformation system of switchgrass is still in urgent need.…”
mentioning
confidence: 99%
“…So far no genetic transformation of upland cultivars has been reported. Even callus regeneration is very difficult to achieve (Song et al 2012;Nageswara-Rao et al 2013). Thus, establishment of a highly efficient and amenable plant regeneration and transformation system of switchgrass is still in urgent need.…”
mentioning
confidence: 99%
“…Prolonged subculture of callus, especially using the synthetic auxin 2,4-dichlorophenoxyacetic acid (2,4-D), turns embryogenic cells into non-embryogenic cells resulting in the loss of regeneration ability, and also leads to somaclonal variations, such as albinism (Karp 1994;Vasil and Vasil 1994). Although both Type I and Type II embryogenic callus cultures of switchgrass have been established from various explant sources, i.e., mature caryopsis, young leaf, immature inflorescence and young seedling (Alexandrova et al 1996;Denchev and Conger 1994;Song et al 2012), reports on the longevity of embryogenic cells and the occurrence of somaclonal variations are limited. Burris et al (2009) reported that inflorescence-derived Type II callus could be maintained for more than 6 months, while the embryo viability of Type I callus was limited to less than 2 months.…”
mentioning
confidence: 99%
“…Seo et al (2010) induced embryogenic callus of 'Blackwell GR63' , although the frequency of shoot regeneration was low (10.9% of calli inoculated). Song et al (2012) reported that herbicide-or hygromycin-resistant calli were induced from inoculated seedling segments of 'Cavein-Rock' but no transgenic shoots were regenerated. Very recently, Liu et al (2015) observed "shell-core" structure within a clump of caryopsis-derived callus of switchgrass cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Different genotypes within a cultivar affect the transformation efficiency (Ogawa et al 2014;Somleva et al 2002) and potentially affect characteristics of transgenic plants that carry the same transgene(s). Seedling-derived callus has been induced and used for transformation (Song et al 2012), although these callus lines also comprise different genotypes. Inflorescences can be obtained from vegetatively propagated plants for callus induction, and thus are a suitable explant source from which to induce callus and transformants derived from a single genotype.…”
mentioning
confidence: 99%